Distributed Resilient Optimal Current Sharing Control for an Islanded DC Microgrid Under DoS Attacks - Lian, Zhijie; Guo, Fanghong; Wen, Changyun; Deng, Chao; Lin, Pengfeng (IEEE transactions on smart grid, 2021)
For DC microgrids (MGs), cyber attacks of distributed secondary control system result in communication faults and thus, cause serious stability and cyber-security issues. In this paper, the cyber-security control problems for current sharing and voltage restoration of an islanded direct-current (DC) MG under denial-of-service (DoS) attacks are addressed. To ensure the stable system operation under DoS attacks, a distributed resilient control method is proposed in the secondary control layer. Subject to DoS attacks, the proposed control method does not only achieve bus voltage restoration but also realize the optimal current sharing optimization calculated by the tertiary layer all the time. Besides, different from most existing secondary control methods with a fixed sampling rate, a new resilient sampling mechanism is designed in the secondary layer to improve the security of the whole system against DoS attacks. The theoretical analysis proves that the proposed distributed resilient controller, which is easy for implementation, can still ensure the stability of the overall DC MG system under DoS attacks. Based on our theoretical analysis, a guideline for controller parameter selection can be used for the MG system design in the planning phase, which could enhance the safety of real-time operation. To test the proposed control method, a DC MG test system is built in a controller-hardware-in-the-loop (CHIL) testing platform. The effectiveness and robustness of our proposed control strategy is validated by the CHIL results.